Professiogram teacher distance learning course in postgraduate teacher education - Vasil'chenko L.V (Kharkov National Pedagogical University, 2010)
Assignment of training teachers to establish a correspondence between increasing social demands of professional roles and the lack of its willingness to perform these functions. Implementation of training of teachers in remote form accompanied by the emergence of new actors of the educational process, which possess specific functions. In the process of creating a regional model of training teachers in remote form defines the basic knowledge and skills that allow teachers to provide a high level of continuing education of teachers.